Therapeutic Potential of Small Molecule Inhibitors. Issue 5 (10th January 2017) - Khera, Nimmish; Rajput, Sandeep
ABSTRACT: Within the last two decades, the advancement in cellular and cancer biology research can be defined by a few foundational pillars—one of the most important ones being the advent of small‐molecule inhibitors (SMIs). Due to their several advantages over contemporary cytotoxic drugs, these engineered molecules have not only shed light on a much deeper understanding of the cellular microenvironment and signal transduction pathways, they have also provided hope of achieving clinical benefits of better patient tolerability while surpassing the efficacy of chemotherapeutic agents. It is, therefore, no surprise that research and development of SMIs has witness a steady surge amongst pharmaceutical industries and research institutions. It is, however, safe to assume that the current applications of SMIs are the mere tip of a yet‐inconceivable iceberg. J. Cell. Biochem. 118: 959–961, 2017. © 2016 Wiley Periodicals, Inc.